Quo vadis Farmer Sales? The Experience of a Survey in Hungary - Laura Bertalan; Renáta Inzsöl; Judit Hegedüs; Ferenc Jankó (Naše gospodarstvo/Our economy, 2019)
Direct sales by farmers gained acceptance in Hungary following the incursion of healthy eating and the enhancement of local economic development efforts. Conducting questionnaire surveys and interviews, our research investigated the means through which locally produced goods reach consumers, e.g., short food supply chains, as well as the farmers’ motivations and the necessary developments. According to the main results, personal direct consumer relations are vital for local farmers; however, advanced sales channels are not popular nor fully developed in Hungary. Only the capital city shows some development here, catalysing and stimulating the domestic market and consumer behaviour. On the other hand, the age structure of local farmers or the lack of knowledge hinder the advent of advanced sales channels. Nevertheless, there is a continuous and immanent need for development in this sector; although, the recent conditions of subsidies unfortunately do not support small scale local farmers.